1996
DOI: 10.1016/0016-7061(95)00079-8
|View full text |Cite
|
Sign up to set email alerts
|

Lateral solute mixing processes — A key for understanding field-scale transport of water and solutes

Abstract: Flühler, H., Durner, W. and Flury, M. 1995. Lateral Solute Mixing Processes-A Key for Understanding and Modeling Field-Scale Transport of Water and Solutes. Geoderma, 00: 000-000.Lateral mass exchange mechanisms affect the spreading of solutes in the main direction of flow. Modeling vertical solute spreading requires therefore an understanding of the lateral transport across regions of varying velocities. Experimental observations show that the variable extent and rates of lateral mixing cause dramatically dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 56 publications
1
91
0
Order By: Relevance
“…An operational definition of preferential transport is a mixing regime that is not convective-dispersive, which assumes complete mixing in the directions transverse to the flow (Flühler et al, 1996). For a convective-dispersive mixing regime, the transport is described by the CDE.…”
Section: Methodsmentioning
confidence: 99%
“…An operational definition of preferential transport is a mixing regime that is not convective-dispersive, which assumes complete mixing in the directions transverse to the flow (Flühler et al, 1996). For a convective-dispersive mixing regime, the transport is described by the CDE.…”
Section: Methodsmentioning
confidence: 99%
“…However, especially tracer experiments in soils (e.g. Flühler et al, 1996) showed a lower effective porosity than the total porosity or even a partitioning into a mobile and immobile fraction. HillVi simulates transport in several domains.…”
Section: The Model Approach For the Virtual Experimentsmentioning
confidence: 98%
“…Constructed soil columns, steady state flow Similar to investigations of water flow, studies of preferential solute transport involved repacked soil columns with artificial PF paths. Due to the impact of lateral concentration equilibration on solute transport in the vadose zone (Flühler et al, 1996), a common theme was the effect of the solute mass transfer term on PNE transport simulations. Steadystate flow conditions are considered below.…”
Section: Modelling Of Tracer Transport In Preferential Flow Systemsmentioning
confidence: 99%